SOIL AS A FACTOR INFLUENCING THE MANGROVE FOREST COMMUNITIES IN TALIDENDANG BESAR, RIAU - CECEP KUSMANA (SEAMEO BIOTROP, 1991)
One transect of 10 m x 900 m was constructed perpendicular to the sea edge to know the pattern ofmangrove forest communities from the sea edge through the inland area. Then, one sample plot of 50 m x 50 mwas established at each forest community to explore its vegetation structure and soil characteristics. The results show that in Talidendang Besar area, there are three mangrove forest communities stretchingfrom the sea edge to the inland, namely Bruguiera parviflora, B. sexangula and B. sexangula-Nypa fruticans.The soil factors such as pH.EC (electrical conductivity), % K, % Na, C-organic, N-total, NH4 (ammonia), andCEC (cation exchange capacity) were regarded important in influencing the pattern of the mangrove forestcommunities.